2019
DOI: 10.14710/jksa.22.4.129-135
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Stability of Trivalent Cations Doped Zirconia through Atomistic Modeling

Abstract: The aim of this research was to study the stability of the structure of the ZrO2 doped with trivalent oxide Zr1-xMxO2-δ (M = La3+, Nd3+, Sm3+, Eu3+, Gd3+, Y3+, Er3+, Yb3+ and Lu3+ through atomistic modelling and bond valence sum method. Short range potential used in this study was Buckinghams’ potential. Result of geometry optimization at constant pressure shown both cell parameters of ZrO2 was in good agreement with experimental results because of the difference was only 0.11%. Increasing the concentration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…Rosyidah et al (2008). For simple compounds that are not layered structures, they can have much smaller lattice parameter differences (La Kilo et al, 2019). The a and b lattice parameters produced in this simulation are not the same as those reported by Miura et al, but Its are consistent with the results of the PbBi2Nb2O9 synthesis reported by Kim et al (2004).…”
Section: Resultssupporting
confidence: 79%
“…Rosyidah et al (2008). For simple compounds that are not layered structures, they can have much smaller lattice parameter differences (La Kilo et al, 2019). The a and b lattice parameters produced in this simulation are not the same as those reported by Miura et al, but Its are consistent with the results of the PbBi2Nb2O9 synthesis reported by Kim et al (2004).…”
Section: Resultssupporting
confidence: 79%
“…The reduction of oxygen takes place to balance the positive charge, leading to a neutrally charged Mg-doped ZrO 2 without free electrons [ 40 ]. Oxygen vacancies in the zirconia lattice can reduce the transformation temperature of the transition or metastable phase, and stabilize and increase the concentration of the tetragonal phase in the Zr-ZrO 2 binary system region [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…BJ. Habibie,Gorontalo,Indonesia Energi kisi sangat penting untuk mengetahui kestabilan fasa suatu kristal padatan melalui simulasi (Dove, 2008;La Kilo et al, 2020;La Kilo, Umamah, & Laliyo, 2019).…”
Section: Hubungan Kestabilan Dan Konduksi Ion Pada Ceria Terdoping Do...unclassified